The "4PS" of traditional Balinese waroengs - Trianasari, ,; Dharma, Agus; Yudiaatmaja, Fridayana (2014)
This paper presents an exploratory type of study aimed to understand the implementations of the 4Ps of the marketing mix in traditional Balinese waroengs. The study was conducted in Denpasar and Gianyar, Bali. Waroengs that provide only Balinese traditional culinary in Bali has been growing rapidly.This growth may relate to the trend of busy lifestyle the locals has been increasingly adopting.This phenomenon is likely to also generate the tendency of the people not to always eat at home.While there are options to dine out at some modern fast-food restaurants, the traditional Balinese foods served at waroengs seemed to be preferable for most of the locals.Interviews with Balinese waroeng owners and managers found that mostly the waroengs were traditionally managed. That is, the majority of the management of this type of business did not adopt any professional business and strategic marketing, including the marketing mix. However, interestingly, among other Ps, “product” was in fact carefully considered in the beginning of their businesses which believed as the main factor to sustain their business. Discussion, implementations, and directions for future research are discussed.